Batman and psychology : a dark and stormy knight - Langley, Travis, 1964- (John Wiley & Sons, 2012)
Takes readers into the complex inner world of Batman, a superhero without superpowers, and Bruce Wayne, explaining psychological theory and concepts through the eyes of one of the world's most popular comic book characters.